INCREASED STRESS AMONG YOUNG PEOPLE: EFFECTS OF SOCIAL MEDIA AND WAYS TO REDUCE STRESS - Kazirakhimova Nargiza Kadirjonovna; Qodirova Dilfuza Murodjon qizi (Western European Studies, 2025)
This article analyzes the increase in stress among young people and its causes related to social networks. The biological basis of stress, the role of the hypothalamo-pituitary-adrenal system and the long-term effects of cortisol are highlighted. Also, the impact of social media on self-confidence, cyberbullying and comparison culture on the psychological health of young people is examined in detail. The article recommends effective ways to reduce stress, including exercise, cognitive-behavioral therapy, pharmacological treatment, mindfulness techniques, healthy eating, and promoting quality sleep. These recommendations are aimed at improving the mental and physical health of young people.
Keywords: stress; youth; social networks; cortisol